Prospective examination of psychological risk and maintenance factors for body image distress after mastectomy with immediate breast reconstruction. (September 2022) - Weingarden, Hilary; Wilhelm, Sabine; Jacobs, Jamie M.; Carrellas, Julia; Cetrulo, Curtis; Austen, William Gerald; Colwell, Amy S.
Abstract: Reconstructive breast surgery aims to improve body image following mastectomy, yet many women experience ongoing body image distress (BID). The relationship between the esthetic outcome of reconstructive surgery with BID has been underexplored in mastectomy. This study aimed to assess whether reconstruction outcome following mastectomy is associated with post-surgery BID, and to examine potential psychological risk and maintenance factors for BID above reconstruction outcome. In 49 women undergoing mastectomy with immediate breast reconstruction, we prospectively assessed hypothesized pre-surgery psychological risk factors and post-surgery maintenance factors for post-surgery BID. Reconstruction outcome was assessed via blind surgeon ratings of post-surgery photographs. Surgeon-rated reconstruction outcome was uncorrelated with BID, or with patients' ratings of surgical outcome. Higher pre-surgery depressive symptoms and lower pre-surgery patient expectations for reconstruction predicted greater post-surgery BID, above reconstruction outcome. Post-surgery body checking also predicted greater BID, above reconstruction outcome. Results suggest that the medical team cannot assume their perception of reconstruction outcome matches the patient's view or degree of BID. If replicated, results point to potential psychological risk and maintenance factors that are stronger predictors of post-reconstruction BID, highlighting opportunities for light-touch prevention and intervention to reduce BID after mastectomy with breast reconstruction. Highlights: Assessed predictors of body image distress after mastectomy with reconstruction. Esthetic outcome of surgery was not related to patients' body image distress. Higher pre-surgery depression predicted greater post-surgery body image distress. Lower expectations for surgical outcome predicted greater body image distress. Body checking behaviors post-surgery corresponded with greater body image distress.